Modifications to the spectrum of radiation from black holes - Johnson, G (2020)
Despite their name, there is clear theoretical evidence that black holes emit radiation. The nature and spectrum of this radiation depends on many features of the black hole and the emitted particles. With the profound implications that black hole evaporation has on our understanding of the marriage of quantum mechanics and general relativity, it is essential to study the details of this radiation in new contexts.